2020
DOI: 10.1177/0036850419898659
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors modulate biofilm formation by Staphylococcus aureus

Abstract: Biofilm formation on indwelling medical devices represents an exclusive evasion mechanism for many pathogenic bacteria to establish chronic infections. Staphylococcus aureus is one of the major bacterial pathogens that are able to induce both animal and human infections. The continued emergence of multiple drug-resistant S. aureus, especially methicillin-resistant S. aureus, is problematic due to limited treatment options. Biofilm formation by S. aureus complicates the treatment of methicillin-resistant S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 77 publications
0
31
0
Order By: Relevance
“…Different environmental factors modulate biofilm formation by S. aureus 16 . During infection, certain pharmacological agents or their derivatives may become a signal for bacteria to promote regulatory changes, and consequently alter gene expression thus allowing S. aureus adaptation to persist in the host.…”
Section: Introductionmentioning
confidence: 99%
“…Different environmental factors modulate biofilm formation by S. aureus 16 . During infection, certain pharmacological agents or their derivatives may become a signal for bacteria to promote regulatory changes, and consequently alter gene expression thus allowing S. aureus adaptation to persist in the host.…”
Section: Introductionmentioning
confidence: 99%
“…Their implantation leads to a host biological response: chronic inflammation, foreign-body response, and host-protein adsorption like fibronectin cover, which also facilitates biofilm development ( Fischer et al, 1996 ; Gibon et al, 2017a , b ; Masters et al, 2019 ). According to the infection site, the proportion of viable adherent bacteria, dead cells, and matrix within the biofilm could be very variable ( Nandakumar et al, 2013 ; Liu et al, 2020 ). Focusing on bone context, primary periprosthetic joint infections (PJIs) after surgery represent approximately 2% of total joint arthroplasty ( Grammatico-Guillon et al, 2012 ; Springer et al, 2017 ; Shoji and Chen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the effect of sugars on the formation of biofilms by strains of S. aureus (Voronkova & Shevchenko, 2017) and S. epidermidis, the following can be noted: the general features of the effect of sugars on strains of both species were a pronounced inhibitory effect at concentrations of 2.5% or more, and an almost neutral reaction at concentration of 0.5%. In experimental research (Liu et al, 2020) it was shown that at concentration of glucose 0.5% with presence of 3.0% NaCl in trypticase soy broth medium for different S. aureus strains variable capacities to form biofilms were observed, which indicates the role of genetic background in biofilm formation. However, there is a tendency to increase in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%